2004
DOI: 10.1074/jbc.m313381200
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling 6 Associates with KIT and Regulates KIT Receptor Signaling

Abstract: Suppressor of cytokine signaling (SOCS) proteins are a family of Src homology 2-containing adaptor proteins. Cytokine-inducible Src homology domain 2-containing protein, SOCS1, SOCS2, and SOCS3 have been implicated in the down-regulation of cytokine signaling. The function of SOCS4, 5, 6, and 7 are not known. KIT receptor signaling is regulated by protein tyrosine phosphatases and adaptor proteins. We previously reported that SOCS1 inhibited cell proliferation in response to stem cell factor (SCF Cytokines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 43 publications
2
87
0
Order By: Relevance
“…SOCS proteins display a degree of specificity for the different receptors. It has been shown that KIT associates with SOCS6 and weakly interacts with SOCS4 and SOCS5 but not with SOCS2 and SOCS3 [18]. Thus, SOCS family proteins appear to be important components that regulate RTK signaling ( Table 2).…”
Section: Socs Proteins In Rtk Regulationmentioning
confidence: 99%
See 4 more Smart Citations
“…SOCS proteins display a degree of specificity for the different receptors. It has been shown that KIT associates with SOCS6 and weakly interacts with SOCS4 and SOCS5 but not with SOCS2 and SOCS3 [18]. Thus, SOCS family proteins appear to be important components that regulate RTK signaling ( Table 2).…”
Section: Socs Proteins In Rtk Regulationmentioning
confidence: 99%
“…SOCS2 has been reported to associate with both wild-type and oncogenic FLT3 but not with KIT [16,18]. The interaction between FLT3 and SOCS2 is mediated through phospho-tyrosine residues Y589 and Y919 in FLT3 and the SOCS2 SH2 domain.…”
Section: Socs2mentioning
confidence: 99%
See 3 more Smart Citations